The Nurse‐Engineer: A New Role to Improve Nurse Technology Interface and Patient Care Device Innovations. Issue 6 (17th September 2018) - Glasgow, Mary Ellen Smith; Colbert, Alison; Viator, John; Cavanagh, Stephen
Abstract: Purpose: The purpose of this article is to describe two innovative biomedical engineering and nursing collaborations designed to educate a new cadre of professionals and develop new knowledge and innovations (robots, patient care devices, and computer simulation). Organizing Construct: Complex health problems demand a highly skilled response that uses teams of professionals from various disciplines. When the biomedical engineering lens is expanded to include the practical perspective of nursing, opportunities emerge for greater technology–nurse interface and subsequent innovation. A joint nursing‐engineering degree program provides the ideal preparation for a well‐informed nurse‐engineer who can explore new and innovative solutions that will improve care and patient outcomes. Approach: A review of the literature provides the background on innovation and engineering in nursing and a rationale for the development of two innovative joint degrees, as well as a description of those programs. Findings: These innovative programs will advance healthcare‐related technology and maximize the potential contribution of the nursing profession in the design and implementation of creative solutions. They also have the potential to increase the skills and knowledge for students enrolled in biomedical engineering or Bachelor of Science in nursing programs individually, providing them with interdisciplinary training and exposure. Clinical Relevance: Important patient care improvement opportunities are missed when nurses are not actively engaged in patient care device innovation and creation. Innovative nurse and engineer collaborations are needed in various forms to leverage nurse ingenuity and create patient care innovations.